Immunoadjuvant-functionalized metal-organic frameworks: synthesis and applications in tumor immune modulation - Zhao, Chen; Song, Weihua; Wang, Jianing; Tang, Xiaoying; Jiang, Zhenqi (Chemical communications (Cambridge, England), 2025)
Cancer immunotherapy, which leverages the body's immune system to recognize and attack cancer cells, has made significant progress, particularly in the treatment of metastatic tumors. However, challenges such as drug stability and off-target effects still limit its clinical success. To address these issues, metal-organic frameworks (MOFs) have emerged as promising nanocarriers in cancer immunotherapy. MOFs have unique porous structure, excellent drug loading capacity, and tunable surface modification properties. MOFs not only enhance drug delivery efficiency but also allow for precise control of drug release. They reduce off-target effects and significantly improve targeting and therapy efficacy. As research deepens, MOFs' effectiveness as drug carriers has been refined. When combined with immunoadjuvants or anticancer drugs, MOFs further stimulate the immune response. This improves the specificity of immune attacks on tumors. This review provides a comprehensive overview of the applications of MOFs in cancer immunotherapy. It focuses on synthesis, drug loading strategies, and surface modifications. It also analyzes their role in enhancing immunotherapy effectiveness. By integrating current research, we aim to provide insights for the future development of immunoadjuvant-functionalized MOFs, accelerating their clinical application for safer and more effective cancer treatments. This review explores the synthesis, drug loading, and surface modifications of metal-organic frameworks (MOFs), highlighting their role in improving cancer immunotherapy and paving the way for safer and more effective treatments.